POLA SPASIAL DAN TREN KEMISKINAN DI INDONESIA TAHUN 2015-2020 - Sekar Pratiwi; Lutfi Setianingrum (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
The National Medium Term Development (RPJMN) 2020-2024 prioritizes the concept of Sustainable Development (SDGs) and the main target is poverty, this indirectly means that poverty is an important thing that must be prioritized for handling. Achieving common prosperity is a reflection of the success of development that is expected by every country in general, including Indonesia. Prosperity can be measured by a decrease in the level of poverty which if the prosperity of an area increases, it means that there is a decrease in the level of poverty. This paper aims to map the pattern of poverty at two points in time, namely 2015 and 2020 between regions in Indonesia. In mapping poverty patterns and trends, the spatial analysis method is used to determine the distribution pattern of poverty between regions in Indonesia. As a result, there are various patterns of poverty ranging from very low to very high class, with poverty in the east being higher than in the west. Based on the changing trend, regions with high poverty rates such as Papua Island actually had the largest poverty reduction from 2015 to 2020 but this has not been able to change their position into regions with the highest poverty rates.